2014
DOI: 10.1080/1064119x.2014.953232
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sediments for Sustainable Development: State of the Art

Abstract: Sediments are the particulate matter that are transported by the flow of water and eventually get deposited at the bottom of water bodies, such as oceans, rivers, lagoons, and so forth. The deposition of these materials due to continued intervention of natural as well as anthropogenic activities is a serious concern as the storage capacity (or health) of the system is reduced or otherwise affected. Keeping in view the emerging challenges associated with proper disposal and subsequent utilization of sediments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 159 publications
(204 reference statements)
0
5
0
Order By: Relevance
“…Sewage sludge is composed of significant amounts of nutrients, such as phosphorus (0.5%-0.7% of total solids) and nitrogen (2.4%-5% of total solids), in the form of protein compounds, which can be employed to produce fertilisers [140][141][142]. Taking into account that phosphorus is a finite resource extracted mainly from rocks located in a few regions of the world, and the high cost of commercial fertilizers, the recovery of nutrients from sewage systems is gaining attention to improve sustainability in agricultural production [112].…”
Section: Nutrientsmentioning
confidence: 99%
“…Sewage sludge is composed of significant amounts of nutrients, such as phosphorus (0.5%-0.7% of total solids) and nitrogen (2.4%-5% of total solids), in the form of protein compounds, which can be employed to produce fertilisers [140][141][142]. Taking into account that phosphorus is a finite resource extracted mainly from rocks located in a few regions of the world, and the high cost of commercial fertilizers, the recovery of nutrients from sewage systems is gaining attention to improve sustainability in agricultural production [112].…”
Section: Nutrientsmentioning
confidence: 99%
“…The physico-chemistry of mangrove and wetland soils is significant towards the stability of soil living organisms [22] and plays key role in the soil-plant trophic pathway. Thus, the degradation of soil chemical composition through the application of fire can impact revealed that the concentration of iron was the highest because of the sedimentary makeup of the base rock of the coastal environment as shown by previous studies in that location [3] [23].…”
Section: Comparison Between Metal Concentrationmentioning
confidence: 99%
“…Over 500 million m 3 of dredged silt is produced each year [3]. This silt has a high moisture content, low strength, poor stability, low loading capacity, and contains large amounts of pollutants [4][5][6]. Dredged silt cannot be directly landfilled and, if not properly handled, can easily cause secondary pollution [7][8][9].…”
Section: Introductionmentioning
confidence: 99%